. PENERAPAN METODE PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA KRITIS SISWA KELAS V SDN NO 166 INPRES BONTORITA KABUPATEN TAKALAR: . - Dina Fakhriah Azhanii; Syekh Adiwijaya Latief; Rahmatiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the implementation of the project-based learning method in improving the critical reading skills of fifth-grade students at SDN No. 166 Inpres Bontorita, Takalar Regency. The research was conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were 24 fifth-grade students. The research instruments included a critical reading skills test, observation sheets, and a project assessment rubric. The results of the study showed that the percentage of students’ mastery in cycle I was 47.83%, which then significantly increased to 91% in cycle II. This improvement covered the ability to identify main ideas, distinguish between facts and opinions, draw conclusions from the text, and provide logical responses. The success was influenced by students’ active engagement in the learning process, the relevance of the material to everyday life, and the high motivation generated by the opportunity to publish their work. Therefore, the PjBL method is effective in enhancing the critical reading skills of fifth-grade students and can serve as an alternative learning strategy that encourages active participation and critical thinking.